Prevalence of overweight and obesity with their associated factors among Iranian students in Kuala Lumpur, Malaysia - Babazekri, Leila (2014)
Background: In recent decades, the prevalence of obesity in children and adolescent has risen worldwide. A high prevalence of adolescence overweight and obesity cases has been reported in developing countries undergoing nutritional transition and developed countries. Adolescents overweight and obesity usually lead to adulthood overweight and obesity. The aim of this study was to investigate the prevalence of overweight and obesity and its associated risk factors among Iranian students age 14 to 18 attending Iranian schools in Kuala Lumpur. Methodology: A cross sectional study was conducted among 161 students age 14 to 18 years old from 5 Iranian schools. Simple random sampling method used for data collection. A validated self-administrated questionnaires with 4 sections including socio demographic factors, psychological factors (depression, anxiety, stress), eating behavior (emotional, external, restrained) and physical activity. Data was analyzed by SPSS version 21. Result: Prevalence of overweight and obesity was 49.7%.There is a significant difference in stress (t=-4.72, p=0.001), depression (t=-5.44, p=0.001), anxiety (t=-2.76, p=0.007), emotional eating (t=-5.38, P=0.001) and physical activity (X2=14.964, P=0.0001) among overweight and obese students with non-overweight and obese students. Multiple logistic regression analysis showed that physical activity OR=0.29, 95% CI (0.14-0.62) is a protective factor for overweight and obesity among students and Stress OR=1.14, 95% CI (1.03-1.25), depression OR=1.11, 95% CI (1.3-1.9), emotional eating OR=1.13, 95% CI (1.06-1.20) contributed significantly as a risk factor for overweight and obesity among respondents. Conclusion: The present study reported high prevalence of overweight and obesity among Iranian students in secondary and high school in Kuala Lumpur. There is therefore an urgent need to set up most intervention programs targeting good diet habits and physical activity and psychological consultation for Iranian adolescents in schools in Kuala Lumpur.